أحكام الضمانات في الصكوك بين المقاصد والشروط - العايدى، علي بن حسين (جامعة المدينة العالمية, 2018)
The purpose of this study is to look at the contracts of guarantees in the Islamic sukuk applied by Islamic banks in order to know their conformity with the provisions of the Shariah and its purposes in form and content. The question is whether guarantees contracts in the sukuk currently prevailing in Islamic banks achieve the purposes of shari'a and the objectives and objectives of the Islamic economy. Therefore, it was necessary to explain the approach of jurists in correcting contracts, and to show the great impact of the purposes of legitimacy in the field of governance on the developments of banking transactions, clarifying the purposes of contracts before the judgment, and activating the rules of transactions, and then provide a legitimate treatment of the problem of guarantees in the sukuk, Analytical Descriptions to reach this goal, where the contract of guarantees in force in Islamic banks is described, and then analyzed the components of this contract and the mechanisms of their application to consider their approval of the purposes of Islamic law.
يهدف هذا البحث إلى النظر في عقود الضمانات في الصكوك الإسلامية التي تطبقها المصارف الإسلامية من أجل معرفة مطابقتها لأحكام الشريعة ومقاصدها شكلاً ومضموناً، وهنا يتطرق الإشكال، هل عقود الضمانات في الصكوك السائدة الآن في المصارف الإسلامية تحقق مقاصد الشريعة وأهداف الاقتصاد الإسلامي وغاياته؟ ولهذا كان لابد من بيان منهج الفقهاء في تصحيح العقود، وإظهار الأثر البالغ للمقاصد الشرعية في مجال الحكم على مستجدات المعاملات المصرفية، مع إيضاح مقاصد العقود قبل الحكم عليها، وتفعيل القواعد الخاصة بالمعاملات، ثم تقديم معالجة شرعية لإشكالية الضمانات في الصكوك، وقد اعتمد الباحث المنهج الوصفي التحليلي للوصول إلى الهدف المذكور، حيث يتم وصف عقد الضمانات المعمول بها في المصارف الإسلامية، ثم تحليل مكونات هذا العقد ومآلات تطبيقها للنظر في موافقتها لمقاصد الشريعة الإسلامية.
Keywords: الشريعة الإسلامية -- الأحكام الشرعية -- مقاصد الشريعة -- الصكوك الإسلامية -- فقه المعاملات